The Influence Of Demonstration Method On Learning Outcomes Of Class 5 B Science Subjects Even Semester Madrasah Ibtidaiyah Negeri 2 Karawang - Sony Kuswandi (International Journal of Education and Digital Learning (IJEDL), 2023)
This type of research is a "quantitative" study with a Group Pretest-Posttest Design. This study aims to determine the effect of the demonstration method on student learning outcomes in class 5 B science subjects in the even semester of Madrasah Ibtidaiyah Negeri 2 Karawang. The subjects of this study were 22 students in grade 5 B. This research was conducted using a test of learning outcomes. The collected data were analyzed quantitatively using descriptive statistics and inferential statistics. The results of the descriptive statistical data show that there is an influence on student learning outcomes which is indicated by the difference in the average score of students which is 51,41 on the pre-test while on the post-test it is 68,23 which means that the acquisition of the score is in the very good category. While the results of the inferential statistical data show that the sig value at the pretest and posttest is 0.001. If the results of the hypothesis testing show 0.001 <0.05, it can be concluded that H0 is rejected and H1 is accepted. Based on the results of the two analyses, it can be concluded that learning methods affect student learning outcomes in grade 5 science subjects even semester at Madrasah Ibtidaiyah Negeri 2 Karawang.